Measurement of plasma gentamicin concentrations postchemical ciliary body ablation in dogs with chronic glaucoma. (17th February 2015) - Rankin, Amy J.; Lanuza, Rick; KuKanich, Butch; Crumley, William C.; Pucket, Jonathan D.; Allbaugh, Rachel A.; Meekins, Jessica M.
Abstract: Objective: To investigate the absorption of gentamicin into the plasma after an intravitreal injection in dogs and to report the success rate of this procedure in lowering the intraocular pressure. Animals: Twenty‐four client‐owned dogs with chronic, end‐stage glaucoma. Procedures: Dogs received a unilateral (22) or bilateral (2) intravitreal injection of 25–40 mg of gentamicin (mean ± SD dose 2.57 ± 1.65 mg/kg and range 0.61–7.50 mg/kg) and 1 mg of dexamethasone per eye. Blood samples were collected at various time points following the intravitreal injection. Plasma concentrations of gentamicin were determined by liquid chromatography and mass spectrometry. Results: The total plasma concentration of gentamicin ranged from 0.21 to 9.71 μg/mL (mean ± SD 2.15 ± 2.03). The mean gentamicin C MAX was 2.29 μg/mL at 2.54 h with a terminal half‐life of 9.8 h. The success rate of the chemical ablation procedure was 86.4% (19/22 eyes) in dogs that had at least 1 month of follow‐up. Conclusions: Intravitreal injection of gentamicin in eyes with chronic glaucoma resulted in detectable plasma levels in dogs and was successful in lowering the intraocular pressure in 86.4% of the eyes after the first procedure.